Teachers' Continuing Professional Development: Action Research for Inclusion and Special Educational Needs and Disability - Geraldene Codina; Deborah Robinson (MDPI AG, 2024)
In 2022, the authors of this paper were awarded with three years' government funding to support seventy-five English schools and Further Education colleges with the running of their own Action Research for inclusion and special educational needs projects (ISEND). Based on the funder's interest in the identification and scaling-up of the evidence-base for SEND practice, this reflective account analyzes the evidence-base drawn upon and created by the Action Researchers for ISEND and the efficacy of the approach. Adopting an interpretivist, qualitative approach to content analysis, this paper analyzes data from the first seven completed Action Research for ISEND projects. Aligned with Dewey's scientific model of reflection, analysis shows the Action Researchers for ISEND draw upon a complex synthesis of contextualized understanding, broadened horizons (including collaborative working and study), deepened and/or reshaped understandings, and data analysis to form their theorizations of praxis. Bearing no relation to evidence-based practice, the Action Researchers for ISEND adopt a constructivist ontology towards the inclusion of children with SEND, which challenges positivistic paradigms of "what works" in SEND and embeds a praxis of democracy which frequently includes the voices of learners with disabilities in decision making processes.